How does Adamkiewicz artery influence blood supply to the fetal spinal cord? - Polaczek, Mateusz; Maslanka, Mateusz; Skadorwa, Tymon; Ciszek, Bogdan (Italian Journal of Anatomy and Embryology, 2015)
Adamkiewicz artery became important in clinical practice since it was noticed that its damage during aorta aneurysm repair surgery can sometimes lead to distal spinal cord ischemia. The complexity of anatomical variations can be related to the development of spinal cord arteries. The aim was to describe topography of Adamkiewicz artery and its relations to the anterior spinal artery in fetuses. The study was carried on 4 Batson’s resin corrosion casts and 24 formalinfixed fetuses injected with dyed gelatin or latex aged 15-24 weeks gestational age. In fixed specimens vertebral canals were dissected, the anterior spinal artery was traced and Adamkiewicz artery localized. Arteries were photographed and digitally measured. Data were afterwards statistically analyzed. Anterior spinal artery was duplicated in 3/28 cases. There were from 1 to 3 Adamkiewicz arteries per specimen, mean 1.71. No relation was found between the number of Adamkiewicz artery and age. In 37/48 cases Adamkiewicz artery emptied into the anterior spinal artery on the left side. Mean degree of narrowing in anterior spinal artery (diameter of the anterior spinal artery above junction with Adamkiewicz artery divided by its diameter under that junction) was 76.74%. The diameter of Adamkiewicz artery was also correlated linearly with the degree of narrowing of anterior spinal artery (r=0.68; p<0.05). The arteries of the anterior aspect of thoracolumbar spinal cord in the 2nd trimester of pregnancy represent the adult pattern. A potentially great impact of Adamkiewicz artery on the distal spinal cord circulation may be postulated on the basis of these morphological data.